You are what you eat and how you digest it! A discussion on inflammatory efferocytosis - Tanzer, Maria C. (Frontiers in Cell and Developmental Biology, 2023)
Efferocytosis is a process by which professional phagocytes – macrophages – remove dead or dying cells. It is considered anti-inflammatory, as the removal process reduces potential inflammatory molecules originating from dead cells and results in the reprogramming of macrophages to an anti-inflammatory state. However, engulfment of infected dead cells, deregulated phagocytosis and perturbed digestion of apoptotic bodies induce inflammatory signalling pathways during efferocytosis. The affected inflammatory signalling molecules and the mechanism of activation are largely unknown. I discuss how the choice of dead cell cargo, the type of ingestion, and the digestion efficiency can influence phagocyte programming in the context of disease. I also present the latest findings, highlight knowledge gaps, and suggest experimental approaches to fill them.